2009
DOI: 10.1002/app.29659
|View full text |Cite
|
Sign up to set email alerts
|

Effect of damp‐heat aging on the structures and properties of ethylene‐vinyl acetate copolymers with different vinyl acetate contents

Abstract: We reported herein the damp-heat aging of ethylene-vinyl acetate copolymers (EVA) with different vinyl acetate (VAc) contents simultaneously for weeks. The aging was carried out under temperature of 40 C and relative humidity of 93% in air atmosphere. The changes of copolymers' structures and properties were investigated by means of FTIR, wide angle X-ray diffraction (WAXD) and differential scanning calorimetry (DSC) and mechanical tests. CI values derived from ATR-FTIR spectra have a decrease when aging time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 29 publications
0
35
0
1
Order By: Relevance
“…Khonakdar et al have studied the melting and crystallization characterizations of EVA in the range of −75°C to 175°C and showed that the weight fraction of crystallinity reduces as a result of polymer chain crosslinking. Moreover, Shi et al have reported the thermal analysis results of EVA. In this study, the primary and secondary crystallization of EVA chains have been demonstrated by two adjacent peaks in differential scanning calorimetry (DSC) thermograms, which are found to be related to the presence of bulky vinyl acetate (VAc) groups in the copolymer.…”
Section: Introductionmentioning
confidence: 99%
“…Khonakdar et al have studied the melting and crystallization characterizations of EVA in the range of −75°C to 175°C and showed that the weight fraction of crystallinity reduces as a result of polymer chain crosslinking. Moreover, Shi et al have reported the thermal analysis results of EVA. In this study, the primary and secondary crystallization of EVA chains have been demonstrated by two adjacent peaks in differential scanning calorimetry (DSC) thermograms, which are found to be related to the presence of bulky vinyl acetate (VAc) groups in the copolymer.…”
Section: Introductionmentioning
confidence: 99%
“…The recorded thermogram revealed two broad endothermic peaks attributed to two types of crystallites of various size and lattice defects, Figure 1. Shi et al [17] reported that for EVA the peaks were located in two ranges -lower transition temperature was situated at 40-60°C and higher transition temperature in the range of 80-90°C. Generally, it is assumed that the larger crystals of better-defined structure show higher melting temperatures which in the case of studied EVA insulation corresponds to the transition showing maximal temperature (T m ) at about 89°C.…”
Section: Resultsmentioning
confidence: 99%
“…Due to little discrepancy among dispersion and size of SmBO 3 and ATO, it is concluded that mechanical properties of EPDM are largely dependent on crosslink density 26. According to literature, the crystallinity of EVA would influence the mechanical properties of EVA resin 7. The increase of VA content could retard the vulcanization of EPDM/SmBO 3 /EVA composites, and then reduce the crosslink density.…”
Section: Resultsmentioning
confidence: 99%
“…However, at high VA content, the VA groups could prevent polyethylene chains from packing into the crystal lattices 6. It is reported that the increase of crystallinity of EVA could enhance the hardness and tensile strength of EVA resin 7, 8…”
Section: Introductionmentioning
confidence: 99%